TINJAUAN JURIDIS KEBIJAKAN PENGHEMATAN AIR TANAH DI PROVINSI DIY - Lucia Setyawahyuningtyas (Kajian Hukum, 2018)
Excessive use of groundwater in the building environment, both government buildings and commercial buildings produce negative impacts, especially on decreasing groundwater levels and groundwater quality. To maintain the availability of ground water, the Indonesian government through Presidential Instruction No.13 of 2011 concerning Energy and Water Savings, and the ministerial regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia in 2012 No. 15 of 2012 concerning the Saving of the Use of Ground Water and the Decree of the Minister of Public Works No. 12/PRT/M/2013 concerning the Saving of the Use of Water Originating from Organizers of Drinking Water Supply Systems in Government Agencies, Local Governments, State Owned Enterprises and Business Entities Regional Property. As a derivative of these two policies, the DIY Government has a policy on saving groundwater as stipulated in Governor Regulation No. 47 of 2014 concerning the Procedures for Saving Groundwater Use. This study aims to provide information on the extent to which the regional policy can be applied and analyze the factors that become obstacles in the implementation of the responsibilities of the DIY government to save groundwater. This study uses qualitative and quantitative methods through the collection of actual data and information as well as judicial-engineering approaches with the support of primary and secondary data related to the implementation of groundwater saving policies in DIY Province. The results of the study show that the main obstacle of water-saving policy in DIY Province is that most local government agencies have not made efforts to save groundwater. The main factor of this failure is because there are still no detailed engineering explanations contained in the article so that the legal subject still does not understand the reference to monitor the savings target.